CCl4 systems’ lifetime with Ng (Ng= He, Ne and Ar), O2, D2O and ND3 (Research, Society and Development, 2022)
The systems’ properties involving noble gases have helped a lot in the development of modeling techniques and standard grades for experimental studies. The objective of this work was to calculate the lifetime of molecular systems formed by helium, neon, argon, dioxygen, deuterated water, deuterated ammonia and carbon tetrachloride (He - CCl4, Ne - CCl4, Ar - CCl4, O2 - CCl4, D2O - CCl4 and ND3 - CCl4). For this, it was used Slater's theory, which consists in an absolutely dynamic formulation, with a complete vibrational analysis of the complexes. The first rovibrational energy level (E0,0) and the vibration frequency (ωe) used were obtained via Discrete Variable Representation and Dunham methods, respectively. The results obtained by both Lennard-Jones (LJ) and the Improved Lennard-Jones (ILJ) analytical forms show that all systems are stable, and the lifetime calculated from the ILJ is always shorter when compared to the lifetime provided from LJ. The results of this article will help in the understanding of systems involving noble gases, as well as in the understanding of the complicated interactions between water and molecules of biological interest.